2017
DOI: 10.1021/acs.est.7b02530
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Chemical Composition of Global and Regional Population-Weighted Fine Particulate Matter Estimated for 25 Years

Abstract: We interpret in situ and satellite observations with a chemical transport model (GEOS-Chem, downscaled to 0.1° × 0.1°) to understand global trends in population-weighted mean chemical composition of fine particulate matter (PM). Trends in observed and simulated population-weighted mean PM composition over 1989-2013 are highly consistent for PM (-2.4 vs -2.4%/yr), secondary inorganic aerosols (-4.3 vs -4.1%/yr), organic aerosols (OA, -3.6 vs -3.0%/yr) and black carbon (-4.3 vs -3.9%/yr) over North America, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 112 publications
8
70
0
Order By: Relevance
“…The largest relative change in cloud albedo of 16 % between 2000 and 2017, occurs for the assumption of least soluble particles and the smallest updraft velocity. The high sensitivity for these conditions are expected, since both low updraft and less soluble particles will generate few cloud droplets and thus high sensitivity to even moderate changes in cloud droplet number concentration, all in 30 agreement with Twomey, (1991) and Platnick and Twomey (1994). If we assume that the most realistic composition is somewhere between the 50:50 and 90:10 chemical makeup, this would yield a cloud albedo change in the range of 10-12 %.…”
Section: Trends In Potential Ccn Concentration 25supporting
confidence: 78%
See 1 more Smart Citation
“…The largest relative change in cloud albedo of 16 % between 2000 and 2017, occurs for the assumption of least soluble particles and the smallest updraft velocity. The high sensitivity for these conditions are expected, since both low updraft and less soluble particles will generate few cloud droplets and thus high sensitivity to even moderate changes in cloud droplet number concentration, all in 30 agreement with Twomey, (1991) and Platnick and Twomey (1994). If we assume that the most realistic composition is somewhere between the 50:50 and 90:10 chemical makeup, this would yield a cloud albedo change in the range of 10-12 %.…”
Section: Trends In Potential Ccn Concentration 25supporting
confidence: 78%
“…Abovementioned air quality policies mainly targeted sulfur emissions which have led to a general decrease in the anthropogenic emissions of SO 2 since the 1970's (Smith et al, 2011;Klimont et al, 2013). With perhaps the exception of the Indian sub-continent, this decrease appears to continue also through the last decade (Li et al, 2017); US EPA, 2018). Zhao et al (2017), showed that the decrease in SO 2 and other important anthropogenic emissions, such as nitrogen oxides 20 and carbonaceous material, is consistent with the decrease in the trends in dimming observed from space borne instruments.…”
Section: Introductionmentioning
confidence: 99%
“…We, thus, present a (non-exhaustive) comparison of the trend results from this study with some other relevant aerosol trend studies in the literature. The Supplement of Li et al (2017) includes a summary of trends reported in the literature for aerosol optical depth (AOD), PM 2.5 and several aerosol constituents (e.g., sulfate, BC).…”
Section: Comparison With Other Trends and Causalitymentioning
confidence: 99%
“…However, information regarding the health effects of PM 2.5 components is limited, mainly hindered by the sparse or non-existent coverage of ground PM 2.5 speciation monitors. Meanwhile, the changes in PM 2.5 mass concentrations are driven by the variations of its chemical composition that are related directly to precursor emissions [7,8], thus, understanding the spatiotemporal changes of PM 2.5 speciation also helps designing more effective air pollution mitigation measures.…”
Section: Introductionmentioning
confidence: 99%